Rational Design of Covalent Organic Frameworks for Photocatalytic Hydrogen Peroxide Production - Ou, Yang; Zhang, Yifan; Luo, Wen; Wu, Yang; Wang, Yong (Macromolecular rapid communications., 2025)
Photocatalytic production of hydrogen peroxide (H2O2) represents a significant approach to achieving sustainable energy generation through solar energy, addressing both energy shortages and environmental pollution. Among various photocatalytic materials, covalent organic frameworks (COFs) have gained widespread attention and in‐depth research due to their unique advantages, including high porosity, predesignability, and atomic‐level tunability. In recent years, significant progress has been made in the development, performance enhancement, and mechanistic understanding of COF‐based photocatalysts. This review focuses on the latest advancements in photocatalytic H2O2 production using COFs, particularly emphasizing the rational design of COF structures to regulate catalytic performance and exploring the fundamental processes involved in photocatalysis. Based on current research achievements in this field, this paper also discusses existing challenges and future opportunities, aiming to provide a reference for the application of COFs in photocatalytic H2O2 production. Covalent organic frameworks (COFs) offer new opportunities for green, efficient photocatalytic hydrogen peroxide (H2O2) production. This review surveys recent achievements in designing and tuning COF architectures, adjusting band structures, and optimizing surface functionalities to achieve improved H2O2 yields. The discussion highlights emerging strategies, mechanistic insights, and future directions for COF‐based sustainable H2O2 photocatalysis.